2017
DOI: 10.1016/j.foodchem.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of β-sitostanol esters catalyzed by the versatile lipase/sterol esterase from Ophiostoma piceae

Abstract: β-sitostanol esters, used as dietary complement for decreasing cholesterol absorption, have been synthesized at 28°C via direct esterification or transesterification catalyzed by the versatile lipase/sterol esterase from the ascomycete fungus O. piceae. Direct esterification was conducted in biphasic isooctane: water systems containing 10mM β-sitostanol and lauric or oleic acid as acyl donors, reaching 90% esterification in 3h with the recombinant enzyme. The use of molar excesses of the free fatty acids did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…3 shows an enhancement of the reaction yields over the time up to a maximum and, except for the linoleic ester, a more or less sharp decrease in efficiency at longer reaction times. As already reported (Molina-Gutiérrez et al, 2017) this result suggests that successive synthesis and hydrolysis reactions can take place in the reaction tube depending on the total water content at different sampling times. As water and the ester are equimolar reaction products, the more efficient the reaction, the greater the amount of water released into the medium and the probability of reversion to hydrolysis.…”
Section: Experimental Approach For Central Composite Design (Ccd)supporting
confidence: 83%
See 2 more Smart Citations
“…3 shows an enhancement of the reaction yields over the time up to a maximum and, except for the linoleic ester, a more or less sharp decrease in efficiency at longer reaction times. As already reported (Molina-Gutiérrez et al, 2017) this result suggests that successive synthesis and hydrolysis reactions can take place in the reaction tube depending on the total water content at different sampling times. As water and the ester are equimolar reaction products, the more efficient the reaction, the greater the amount of water released into the medium and the probability of reversion to hydrolysis.…”
Section: Experimental Approach For Central Composite Design (Ccd)supporting
confidence: 83%
“…Four independent variables were examined in different ranges (Table 1): temperature (20-36 ºC), enzymatic dosage (3-15 U mL -1 ), acyl donor concentration (4-60 mM) and reaction time (10-490 min). The experimental ranges -1 and +1 were chosen taking into account the results obtained previously (Molina-Gutiérrez et al, 2017). Four replications of the center point (CP, coded as 0) were carried out, adding axial points in order to adjust the experimental results to a second-order model.…”
Section: Optimization Of the Synthesis Of -Sitostanol Esters By Dirementioning
confidence: 99%
See 1 more Smart Citation
“…It is generally believed that plasma total and LDL cholesterol levels can be reduced up to 20% with a dose of 1.5–3.0 g phytosterol/day in humans (Katan et al, ; Quilez, Garcia‐Lorda, & Salas‐Salvado, ). Many studies in recent years showed that phytosterol had a low solubility in edible oil (Molina‐Gutiérrez, Hakalin, Rodríguez‐Sanchez, Prieto, & Martínez, ), while phytosterol ester was well soluble in lipids, and had same effect with phytosterol to lower plasma total and LDL cholesterol levels (Qianchun et al, ). Therefore, phytosterol ester can be more easily added to various foods, especially fatty foods such as special margarine (Weber, Weitkamp, & Mukherjee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Esterification of phytosterols with fatty acids can decrease their melting point and improve their solubility in oil and fats (Deng et al, ; No, Zhao, Lee, Lee, & Kim, ). A variety of studies have been performed on the esterification or transesterification of phytosterols with fatty acids or fatty acid esters (Cui et al, ; Deng et al, ; Hu et al, ; Molina‐Gutierrez, Hakalin, Rodriguez‐Sanchez, Prieto, & Martinez, ; No et al, ; Zeng et al, ). Our team previously synthesized a series of phytosteryl or phytostanyl fatty acid esters using lipase, ionic liquids (IL), or acid‐surfactant‐combined catalyst as catalyst (He et al, , ; Yang et al, ).…”
Section: Introductionmentioning
confidence: 99%